INOVASI OLAHAN WORTEL DALAM BENTUK PUDING UNTUK PENCEGAHAN STUNTING PADA ANAK-ANAK DI DESA BEKIUNG - Angraini, Tuti; Harahap, Amanda Zachra; Bahari, Syahrial (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2025)
Abstract: Stunting remains a chronic nutritional problem that affects children’s physical growth, cognitive development, and overall quality of life in the future. This condition is commonly found among toddlers in rural areas due to limited nutritional knowledge and the lack of diverse nutritious foods that are easily accepted by children. A community service program in Bekiung Village was implemented under the theme “Application of Carrot Pudding Innovation to Prevent Stunting in Children” as a practical solution to address this issue. The methods involved socialization on stunting prevention, education on balanced nutrition, and demonstration of carrot pudding preparation, which is rich in beta-carotene, vitamins, minerals, and fiber. The main target was mothers with toddlers and young children, aiming to provide an alternative healthy snack that is simple, affordable, and appealing. The results revealed increased awareness among participants regarding the importance of adequate nutrition, as well as their ability to practice carrot pudding making as a supplementary food. This local food innovation has proven effective in enhancing children’s acceptance of vegetables through more attractive forms of preparation. Therefore, carrot pudding application can serve as a relevant, low-cost, and sustainable preventive strategy to support stunting reduction efforts in Bekiung Village.Keyword: Bekiung Village, Child Nutrition, Food Innovation, Carrot Pudding, Stunting Abstrak: Stunting masih menjadi permasalahan gizi kronis yang berdampak pada pertumbuhan fisik, perkembangan kognitif, dan kualitas hidup anak di masa depan. Kondisi ini banyak dijumpai pada balita di pedesaan akibat rendahnya pengetahuan gizi dan terbatasnya variasi makanan bergizi yang mudah diterima anak. Program pengabdian kepada masyarakat di Desa Bekiung dilaksanakan melalui kegiatan “Penerapan Inovasi Olahan Wortel dalam Bentuk Puding” sebagai solusi praktis untuk pencegahan stunting. Metode yang digunakan meliputi sosialisasi mengenai bahaya stunting, edukasi gizi seimbang, serta demonstrasi pembuatan puding wortel yang kaya beta-karoten, vitamin, mineral, dan serat. Sasaran utama kegiatan ini adalah ibu-ibu yang memiliki balita dan anak-anak, dengan tujuan memberikan alternatif camilan sehat yang mudah, cepat, dan ekonomis. Hasil kegiatan menunjukkan peningkatan pemahaman peserta mengenai pentingnya pemenuhan gizi serta kemampuan mempraktikkan pembuatan puding wortel sebagai makanan tambahan. Inovasi pangan lokal ini terbukti mampu meningkatkan daya terima anak terhadap sayuran melalui bentuk olahan yang lebih menarik. Dengan demikian, penerapan puding wortel dapat dijadikan strategi preventif yang relevan, murah, dan berkelanjutan untuk mendukung upaya pencegahan stunting pada anak di Desa Bekiung. Kata Kunci: Desa Bekiung, Gizi Anak, Inovasi Pangan, Puding Wortel, Stunting